One of the Short-Chain Fatty Acids (SCFAs), Sodium Propionate, Can Reduce the Dosage of Sishen Pill in Regulating the Intestinal Microbiota in Diarrhea with Kidney-Yang Deficiency Syndrome - Guo M; Di J; Tan Z; Xiao N; Peng M (Journal of Inflammation Research)
Meifang Guo,1 Jiaxin Di,1 Zhoujin Tan,2 Nenqun Xiao,1 Maijiao Peng1 1School of Pharmacy, Hunan University of Chinese Medicine, Changsha, Hunan, People’s Republic of China; 2Hunan University of Chinese Medicine, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Nenqun Xiao, School of Pharmacy, Hunan University of Chinese Medicine, Changsha, 410208, People’s Republic of China, Email xiaonenqun@sohu.com Maijiao Peng, School of Pharmacy, Hunan University of Chinese Medicine, Changsha, 410208, People’s Republic of China, Email 187267400@qq.comObjective: To investigate the potential mechanisms underlying the combined therapeutic effects of sodium propionate and Sishen Pill and to provide experimental evidence supporting their mode of action.Methods: The method utilized involved the induction of a mouse model of Diarrhea with Kidney-Yang Deficiency Syndrome by administering adenine combined with Folium sennae. After the successful establishment of the model, the mice in the model group were randomly assigned to one of the following treatment groups: natural recovery group, sodium propionate group, 75% Sishen Pill combined with 60 mg/kg sodium propionate group, or Sishen Pill group.Results: The 75% Sishen Pill combined with 60 mg/kg sodium propionate demonstrated significantly better therapeutic effects compared to the Sishen Pill alone and sodium propionate alone groups. The combined treatment significantly improved the behavioral indices of mice (p < 0.05); increased the levels of MUC2 and sIgA (p < 0.01); reduced IL-6 levels (p < 0.05); and improved structural damage in the kidneys and small intestines. Intestinal microbiota analysis showed that 75% Sishen Pill combined with 60 mg/kg sodium propionate significantly increased beneficial bacteria such as Lactobacillus (p < 0.05), while Prevotellamassilia and Maribacter were significantly enriched in this group. Correlation analysis revealed that Lactobacillus and Pediococcus were positively correlated with MUC2 and sIgA, while negatively correlated with IL-6.Conclusion: The 75% Sishen Pill combined with 60 mg/kg sodium propionate significantly alleviates symptoms related to Diarrhea with Kidney-Yang Deficiency Syndrome, enhances the efficacy of Sishen Pill by regulating the intestinal microbiota, boosts intestinal immune function, and reduces intestinal inflammation, providing a new approach for treating Diarrhea with Kidney-Yang Deficiency Syndrome.Keywords: sodium propionate, kidney-yang deficiency syndrome, intestinal microbiota, intestinal inflammation, Sishen Pill